Assessment of Use of Indigenous Maize Storage Practices among Farmers in Anambra State, Nigeria - Ajani, EN; Onwubuya, EA (International Journal of Agricultural Research, Innovation and Technology, 2013)
The study assessed the use of indigenous maize storage practices among farmers in Anambra State, Nigeria. Data for the study was collected by the use of interview schedule from a sample of 60 respondents. Percentage, mean score and standard deviation were used for analyzing data collected for the study. Results revealed that the farmers were using indigenous technologies such as baskets, aerial (over fire) in the kitchen, bare floors, among others in storing maize. The respondents indicated that they stored maize cobs undehusked in order to overcome wastage and obtained information about indigenous storage of maize from parents and fellow farmers. Major problems militating against effective storage of maize include: attack of pests such as rodents and weevils, diseases, termite attack and use of poor quality storage materials. The respondents indicated that use of materials free from termite, clearing of surroundings against fire disaster; use of durable materials treated with insecticides will help to solve the problems. The study recommends that provision of appropriate and affordable storage structures should be made available to the maize farmers in order to avoid wasting of the produce under storage. This will help to ensure food security among rural farm households. DOI: http://dx.doi.org/10.3329/ijarit.v2i2.14014 Int. J. Agril. Res. Innov. & Tech. 2 (2): 48-53, December, 2012